Pengembangan E-Book Interaktif Konsep Dasar IPS berbasis Nilai-Nilai Moderasi Beragama - Hamer, Wellfarina (Tapis: Jurnal Penelitian Ilmiah, 2022)
This study aims to produce interactive digital e-book teaching materials on social studies basic concepts based on religious moderation values ​​and determine student responses to interactive social studies e-books based on religious moderation values. The development of this interactive e-book uses Research and Development (R&D) research methods. The use of the R&D method aims to produce new products or improve existing products. The R&D method that will be used refers to the ten steps of Borg and Gall theory. The results showed that the interactive e-book of social studies basic concepts based on the values ​​of religious moderation received a very high or very decent rating from the validators of material experts, media experts, and religious moderation experts with the criteria for assessing the suitability of content with the curriculum, construction and readability. The small group trial which was given an assessment by 30 students who had taken the social studies basic concept course in the Tadris IPS study program obtained a very high rating and was suitable for use with a percentage of 83.38%.